PENGATURAN HUKUM PIDANA DI BIDANG PERPAJAKAN DAN HUBUNGANNYA DENGAN HUKUM PIDANA UMUM DAN KHUSUS CRIMINAL JUSTICE REGULATION IN THE TAXATION FIELD CRIMINAL AND ITS RELATION TO GENERAL AND SPECIAL CRIMINAL LAW - ., Mudzakkir (Jurnal Legislasi Indonesia, 2011)
Income funds contribution that coming from taxpayers is a significant input of opinionand have a broad significance for the development of the Unitary Republic of Indonesia.One must be concern is the effort to increase awareness of taxpayers to pay taxesand also as the essence of the regulation and the imposition of criminal sanctions inthe field of taxation. The criminal action in the field of taxation is included criminallaw in the field of administration (administrative criminal law or crimes dependent)known simple and flexible in enforcing of the law, as long as the objective of law isreached, the taxpayer would pay tax in accordance with its obligations. The use ofcriminal common law or penal code/law dealing specifically with criminal acts in thefield of taxation is inappropriate and can caused problems in law and justice. Therefore,public crime or specific crime related to the occurrence of a tax crime is a stand-alonewith all the consequences of enforcement. Related to the implementation of corruptionin the criminal acts in the field of taxation, could be run by two models, which eachstand alone and not related to each other, as stipulated in Article 43 A paragraph (3)or tax laws contain provisions referred to in Article 14 Act Number 31 Year 1999 asamended by Act Number 20 Year 2001 on Eradication of Corruption.